2017
DOI: 10.9734/jamb/2017/34060
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Carriers of Enteric Pathogens and the Risk Factors among Food Handlers in a Rural Setting in Nigeria

Abstract: Introduction: Presence of enteric pathogens in humans has been described as one of the most common challenges of developing countries. Materials and Methods: Stool samples were collected from 540 randomly selected workers in the hospitality industry in Etim-Ekpo and were subjected to microscopic and bacteriological examination to detect asymptomatic carriers of enteric pathogens. A structured questionnaire was used to collect additional data from the subjects. Each of these subjects aged between 18 and 56 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…This is consistent with the reported prevalence in a study done in South Ethiopia (10%) [12], Nigeria (17.2%) [13] and India (13.3%) [14]. However, it is higher than the reported prevalence by other studies in Gondar, Ethiopia (3.1%) [15], Addis Ababa, Ethiopia (3.5%) [16], Nigeria (6.9%) [17] and Jordan (7.4%) [18]. The observed differences in rates of bacterial isolation could be attributed to differences in food handling and santiation practice, study period and geographical varation [14, 15].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with the reported prevalence in a study done in South Ethiopia (10%) [12], Nigeria (17.2%) [13] and India (13.3%) [14]. However, it is higher than the reported prevalence by other studies in Gondar, Ethiopia (3.1%) [15], Addis Ababa, Ethiopia (3.5%) [16], Nigeria (6.9%) [17] and Jordan (7.4%) [18]. The observed differences in rates of bacterial isolation could be attributed to differences in food handling and santiation practice, study period and geographical varation [14, 15].…”
Section: Discussionsupporting
confidence: 90%
“…The isolation rate of Shigella species (10.1%) in our study was in agreement with the study conducted in India (9.3%) [14]. Conversely, this finding was lower than the results of a study conducted in Nigeria (15.5%) [19], and higher compared to similar studies conducted in Gondar, Ethiopia (3.1%) [15], Jimma, Ethiopia (0.9%) [7], Nigeria (2.2%) [17], and Iran (0.9%) [20]. This may indicate poor hygien, both personal and food handling practices and may lead to outbreaks of bacillary dysentery to the public [14].…”
Section: Discussionsupporting
confidence: 88%
“…However, the prevalence of Salmonella species in the present study is lower than the prevalence reported from Nigeria (5.5–17%) [22, 23], Arba Minch, Southern Ethiopia (6.9%) [15], Saudi Arabia (3.86%) [24] and Haramaya, Eastern Ethiopia (3.6%) [25]. The finding of current study is high compared to report from Hawassa, Ethiopia [26], Gondar, Ethiopia [27], Makah, Saudi Arabia [28], Jordan [29], Thailand [30], Japan [31], Dilla, Southern Ethiopia [32] and Nigeria [2]. The difference in the prevalence of Salmonella species among food handlers observed across different countries and within in country may be due to laboratory methods used, level of education, economic status, and characteristics of study participants.…”
Section: Discussionmentioning
confidence: 72%
“…Center for Disease Control and Prevention (CDC) identified more than 400 food-related infections, among which 20% are due to food handlers [1]. The spread of disease through food handlers is a common and persistent problem worldwide and food handlers may be carrying a wide range of enteric pathogen and have implicated in the transmission of many infections to the public [2].…”
Section: Introductionmentioning
confidence: 99%